Current oscillations in austenitic stainless steel induced by the presence of chloride ions - Podestá, José J. (1982)
The conditions for current oscillations in austenitic stainless steel (AISI Type 303) in 1M H2SO4, containing CI- ions are given. The periodic oscillations are produced in a close potential range determined at the active-passive transition region. It requires a non-homogeneous distribution of inclusions and carbides at the metal surface and a concentration range of CI- ion where active and passive areas coexist on the metal surface. The constraints at the surface determining these two regions are related to the CI- ion competitive adsorption and the local accumulation of corrosion products. Electrochemical data and SEM observations are correlated.